2017
DOI: 10.1093/ofid/ofx249
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-Defining Illnesses at Initial Diagnosis of HIV in a Large Guatemalan Cohort

Abstract: BackgroundAnecdotal evidence suggests that a high proportion of patients diagnosed with HIV in Guatemala present with AIDS. There remain limited data on the epidemiology of AIDS-defining illnesses (ADIs) in Central America.MethodsWe conducted a retrospective cohort study of all patients living with HIV at the largest HIV clinic in Guatemala. Charts were analyzed for clinical and demographic data. Presence of an ADI was assessed by US Centers for Disease Control definitions; patients who presented with an ADI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The burden of AIDS-defining illnesses, particularly TB and CM are high in sub-Saharan African countries with an estimated rate ranging from 16% to 29%. 10 Our patient had evidence of both CM and disseminated TB, which are the two most common causes of AIDS-related deaths in sub-Saharan Africa. The most unusual presentation in this patient was the occurrence of these two life-threatening opportunistic infections in association with two other equally lethal conditions -severe COVID-19 pneumonia and acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 62%
“…The burden of AIDS-defining illnesses, particularly TB and CM are high in sub-Saharan African countries with an estimated rate ranging from 16% to 29%. 10 Our patient had evidence of both CM and disseminated TB, which are the two most common causes of AIDS-related deaths in sub-Saharan Africa. The most unusual presentation in this patient was the occurrence of these two life-threatening opportunistic infections in association with two other equally lethal conditions -severe COVID-19 pneumonia and acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 62%
“…As shown in our study, and in consonance with previous studies, being older than 50 years at time of diagnosis, was associated with a substantially higher risk of death from CCa ( 9 , 10 ). However, no consistent pattern was observed when 13 African countries were studied ( 57 ). Conversely, age at diagnosis was found to be protective in an Ethiopian study ( 15 ), however, the cohort used for the study had younger women with mean cohort age of 49 years which might have impacted the study finding.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study in Brazil showed that HIV infection did not affect initial treatment response or early mortality in women with cervical cancer, but it did increase relapse after achieving a complete response or remission, and late mortality ( 56 ). Similarly, the immunosuppression linked with HIV/AIDS also increases the susceptibility of CCa patients to other life-threatening AIDS-defining infections and cancers ( 57 ) which adds significant morbidity and increase their mortality risk.…”
Section: Discussionmentioning
confidence: 99%